Study of Diesel-biodiesel Fuel Properties and Wavelet Analysis on Cyclic Variations in a Diesel Engine - Mohd Hafizil, Mat Yasin; R., Mamat; Ali, Obed Majeed; Ahmad Fitri, Yusop; Mohd Adnin, Hamidi; I. M., Yusri; Rasul, Muhammad (Elsevier Ltd, 2017)
Continuous searching in new energy sources has been a crucial issue for sustaining the increasing energy demand. Due to the present economic and social modernization as well as petroleum oil depletion crisis, makespromising alternatives such as renewable energy sources an important choice for the next power generation. Petroleum fuel includesdiesel currently used in power generation, transportation, and industrial sectors. The introduction of biodiesel as a secondary fuel for diesel engines has revolutionized the use of different fuels with fuel blending in current diesel. Though biodiesel-diesel fuel can substitute diesel fuel at an acceptable blending ratio rate up to 20%, fuel properties could be affected with beyond the limit from the engine manufacturer's standard when blending at high volume ratio. Thus, in the present study, the use of the diesel-biodiesel fuel (B20) was investigated corresponding to the fuel properties and engine cyclic variations. Also, the tested fuels include mineral diesel were tested experimentally in a diesel engine with the in-cylinder pressure data measurement for 1000 cycles. These data were analyzed using the coefficient of variation (COV) and wavelet power spectrum (WPS). Fuel properties test results showed significant differences in density and acid value with a significant reduction in viscosity when diesel is blended with biodiesel at 20%. Despite that, the low heating value was significantly affected for B20 compared to pure biodiesel. While as for the wavelet analysis results, the short period oscillations appear periodically in pure biodiesel and mineral diesel, but in contrast, the long and intermediate-term periodicities has are found in B20. Moreover, the spectral power has increased with B20, which attributed significantly to the engine cyclic variations. This characteristic validated the coefficient of variation (COV) for the indicated mean effective pressure (IMEP) time series that B20 produces the lowest fluctuation in cyclic variations compared to other fuels.